The Goal: A Process of Ongoing Improvement - Goldratt, Eliyahu M.; Cox, Jeff (North River Press, 1992)
Over 2 million copies sold! Used by thousands of companies and hundred s of business schools! Required reading for anyone interested in the T heory of Constraints. This book, which introduces the Theory of Constr aints, is changing how America does business. The Goal is a gripping, fast-paced business novel about overcoming the barriers to making mone y. You will learn the fundamentals of identifying and solving the prob lems created by constraints. From the moment you finish the book you w ill be able to start successfully addressing chronic productivity and quality problems.